Uji Efektivitas Antibakteri Ekstrak Brokoli (Brassica Oleracea Var. Italica) Terhadap Pertumbuhan Bakteri Porphyromonas Gingivalis: Eksperimental Laboratoris - Edrizal, Edrizal; Nasri, Muhammad Harits; Kornialia, Kornialia (Fakultas Kedokteran Gigi Universitas Padjadjaran, 2026)
Introduction: Broccoli may serve as a potential antibacterial agent due to its bioactive compounds, including flavonoids, saponins, quinones, tannins, terpenoids, polyphenols, and glucosinolates. These compounds may contribute to antibacterial activity and could provide a natural alternative to conventional antibacterial agents. This study aimed to determine the inhibitory effect of broccoli (Brassica oleracea var. italica) extract on the growth of Porphyromonas gingivalis. Methods: This study employed a laboratory experimental design. Broccoli was extracted using the maceration method with ethanol as the solvent. Antibacterial activity was evaluated using Mueller–Hinton Agar (MHA) medium and the disk diffusion method. The treatment groups consisted of 10%, 30%, and 60% broccoli extract concentrations, with metronidazole as the positive control and dimethyl sulfoxide (DMSO) as the negative control. Antibacterial activity was determined based on the diameter of the inhibition zones. The data were analyzed descriptively and presented in tables. Results: The 10% broccoli extract exhibited weak antibacterial activity, with an inhibition zone of 3.8 mm. The 30% extract showed moderate antibacterial activity, with an inhibition zone of 4.75 mm, while the 60% extract demonstrated strong antibacterial activity, with an inhibition zone of 7.6 mm. The positive control, metronidazole, produced strong inhibition zones at all tested concentrations. Conclusion: All tested concentrations of ethanolic broccoli extract exhibited antibacterial activity against Porphyromonas gingivalis, ranging from weak to strong inhibition. However, the antibacterial activity of the broccoli extract was lower than that of metronidazole.Uji daya hambat ekstrak brokoli (Brassica oleracea var. Italica) terhadap pertumbuhan Porphyromonas gingivalis: studi eksperimenPendahuluan: Brokoli dapat menjadi alternatif antibakteri sebab kandungan di senyawa seperti flavonoid, saponin, kuinon, tanin, terpenoid, polifenol, serta glukosinolat. Brokoli ini berfungsi sebagai antibakteri alami tanpa menyebabkan resistensi apabila dikonsumsi secara terus-menerus. Tujuan dari penelitian untuk mengetahui daya hambat ekstrak brokoli (Brassica oleracea var. italica) terhadap pertumbuhan Porphyromonas gingivalis. Metode: Penelitian yang digunakan yakni eksperimental laboratoris. Teknik ekstraksi yang digunakan yaitu maserasi dengan zat pelarut etanol. Aktivitas antibakteri dengan media Mueller Hinton Agar (MHA) dievaluasi berdasarkan zona hambat memakai metode difusi cakram bersama kelompok perlakuan ekstraksi brokoli 10%, 30%, 60%, kontrol positif metronidazol, dan kontrol negatif DMSO. Uji analisis data dilakukan dengan Rumus perhitungan diameter zona hambat. Hasil: Zona hambat antibakteri ekstrak brokoli kategori lemah pada konsentrasi 10% (3,8 mm), konsentrasi 30% (4,75 mm), dan kategori sedang pada konsentrasi 60% (7,6 mm). Seluruh konsentrasi pada kontrol positif didapatkan zona hambat dalam kategori kuat. Simpulan: Semua konsentrasi ekstrak etanol brokoli yang diuji memiliki efek antibakteri terhadap Porphyromonas gingivalis dengan kategori ringan sampai sedang, namun efeknya belum setara dengan metronidazol.